PENYULUHAN TINDAK TUTUR YANG SANTUN DALAM MEMPENGARUHI ETIKA BERBAHASA ANAK DI RULI BALOI KOLAM, BATAM: Counseling on Polite Speech Acts in Influencing Children's Language Ethics at Ruli Baloi Kolam, Batam - Dairi Sapta Rindu Simanjuntak; Yunisa Oktavia; Fasaaro Hulu (PUAN INDONESIA, 2023)
Language is a means of communication between humans in people's lives in the sound of speech produced by human speech instruments. Language in its function as a means of communication its existence is very important in society. Without language in communicating, between speakers and interlocutors will have difficulty in capturing the communication message. Communication through language allows everyone to adjust to their physical and social environment and to learn the habits, culture and background of the interlocutor. Our culture judges that speaking using polite language will show our true ethics, education, and culture as human beings who are well respected as human beings. Whether or not a speech is polite depends on the size of the politeness of the people speaking a language. Speech in Indonesian is generally considered polite if speakers or speech partners use words that do not contain direct ridicule, do not command directly, and respect others. Good and correct use of language will be necessary in conveying messages to others. Both direct and indirect messages use message characteristics that need to be understood by others. The use of language to communicate is inseparable from the determinants of communication acts and the principles of politeness and realized in communication acts.